Processing results of measurement when determining the rapeseed oil density - Piven, O. M.; Demydov, I. M.; Melnyk, D. M.; Minchenko, O. A. (Софтрейд, 2022)
Therefore, based on the abovementioned studies, tables of the dependence of the density of unrefined rapeseed oil vs. temperature within the temperature range of 273-373 deg K were developed.
Keywords: oil density; unrefined rapeseed oil; technological calculations; Abbe's criterion; Dixon-Gardner and Irwin criteria